1997
DOI: 10.1074/jbc.272.12.7608
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the C-terminal Domain of Human Collagenase-3 (MMP-13) in the Activation of Procollagenase-3, Substrate Specificity, and Tissue Inhibitor of Metalloproteinase Interaction

Abstract: ). The kinetics of activation were not affected by removal of the hemopexin-like C-terminal domain. The specific activities of both collagenase-3 and ⌬ 249 -451 collagenase-3 were found to be similar using two quenched fluorescent substrates, but ⌬ 249 -451 collagenase-3 failed to cleave native triple helical collagens (types I and II) into characteristic one-and three-quarter fragments. It was noted, however, that the ␤1,2(I) chains of type I collagen were susceptible to ⌬ 249 -451 collagenase-3, which indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
238
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 319 publications
(246 citation statements)
references
References 42 publications
6
238
1
1
Order By: Relevance
“…Matrix metalloproteinase -13 (collagenase-3) has been found to have an exceptionally wide substrate specificity when compared with other MMPs (Freije et al, 1994;Knauper et al, 1997). Moreover, it is thought to play a central role in the MMP activation cascade, both activating and being activated by several other MMPs (MMP-14, 2, or 3).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase -13 (collagenase-3) has been found to have an exceptionally wide substrate specificity when compared with other MMPs (Freije et al, 1994;Knauper et al, 1997). Moreover, it is thought to play a central role in the MMP activation cascade, both activating and being activated by several other MMPs (MMP-14, 2, or 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF-a and TGF-b-elicited stimulation of A-5 cell invasion through Matrigel was entirely abrogated by IFN-g most likely due to inhibition of MMP-9 production. However, as MMP-13 also degrades type IV collagen (KnaÈ uper et al, 1997), it is possible that reduction in MMP-13 production also impairs the ability of transformed keratinocytes to invade through basement membrane. Together these observations clearly show, that IFN-g plays an important role in limiting the invasion capacity of transformed keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently investigated the role of IKK-2 in the production of MMPs in the RA synovial membrane. These enzymes play a role in the destructive process of RA by breaking down human cartilage and bone (54)(55)(56). We previously showed that MMP-1 and MMP-3 expression in ex vivo RA synovial membranes is NF-B dependent because AdI B␣ down-regulates their expression (17).…”
Section: Role Of Ikk-2 In Cytokine and Mmp Production In Ramentioning
confidence: 99%